Prevalence and characteristic of young adults with acute myocardial infarction in a single referral centre in Pahang - Mohd Razib, Mohd Zhafri; Draman, Samsul; Abdullah, Aszrin; Ab Rahman, Jamalludin; M. Bakrim, Norbaiyah; Mohd Shah, Azarisman Shah (2019)
Background: Acute myocardial infarction (AMI) is a number one cause of death worldwide. However, there is lack of data regarding young adults with AMI. This study was aimed to measure the prevalence and characteristics of young adults (age between 18-45 years old) with newly diagnosed AMI presented in Hospital Tengku Ampuan Afzan (HTAA), Kuantan, Pahang. Methods: This cross-sectional study was conducted in HTAA from 31st July 2017 to 30th July 2018 involving 818 patients who were diagnosed with AMI. Eighty-four patients were less than 45 years old, and fifty-eight who fulfilled the inclusion and exclusion criteria were recruited for analysis. Results: The prevalence of young adults with AMI was 10.9%. The common risk factors were smoking (N=45, 77.6%) followed by obesity (N=33, 56.9%), increased waist circumference (N=32, 55.2%), hyperlipidaemia (N=29, 50.0%), hypertension (N=20, 34.5%), family history of cardiovascular disease (CVD) (N=20, 34.5%), diabetes mellitus (N=18, 31.0%), and alcohol consumption (N=7, 12.1%). It was revealed that all patients had at least one CVD risk factor. Majority of the patients (N=17, 42.5%) had single coronary vessel involvement and left anterior descending artery was the commonest vessel involved (N=36) in the coronary angiographic findings. Conclusion: There was a significant prevalence of young adults with AMI in Pahang. The commonest risk factor observed was smoking, closely followed by obesity and hyperlipidemia. Thus, the presence of these risk factors in young adults is significant for screening in primary health centre.